Hierarchical nanorods of graphene oxide decorated SnO2 with high photocatalytic performance for energy conversion applications. (15th September 2022) - Perumal, V.; Sabarinathan, A.; Chandrasekar, M.; Subash, M.; Inmozhi, C.; Uthrakumar, R.; Isaev, Abdulgalim B.; Raja, A.; Elshikh, Mohamed S.; Musaed Almutairi, Saeedah; Kaviyarasu, K.
Graphical abstract: Highlights: Graphene oxide decorated tin oxide hierarchical nanorods (HNRs SnO2 @GO) 2 wt% GO decorated HNRs SnO2 @GO sample exhibited better methylene blue. The materials made had better visible light absorption, high crystallinity. GO may enhance SnO2 NP photocatalytic activity by adsorption & electron transport. GO content of 3 wt%, led to decrease the dye degradation efficiency (83%) Abstract: Tin oxide (SnO2 ) hierarchical nanorods are decorated with different weight percentages (1, 2 and 3%) of graphene oxide (GO) were prepared through sol–gel method. The produced hierarchical nanorods (HNRs SnO2 @GO) have a tetragonal rutile structure with considerable crystallinity, according to X-ray diffraction examination. The produced SnO2 @GO nanocomposites encompasses the distinctive bands of SnO2 and GO according to a FTIR investigation. SEM was used to examine the morphology of the produced nanocomposite materials, revealing hierarchal nanoparticles of SnO2 wrapped on graphene sheets. EDX analysis reveals that all the samples are made up of Sn and O elements (for SnO2 ) and Sn, O, and C elements (for SnO2 and GO composite). The photocatalytic performance of the prepared GO decorated SnO2 samples were studied for methylene blue (MB) dye degradation under visible light irradiation. Therefore, the 2% weight of GO with SnO2 exhibits the high degradation efficiency of 96% for MB dye which is applicable for energy conversion devices.